2006
DOI: 10.1111/j.1365-2966.2006.10999.x
|View full text |Cite
|
Sign up to set email alerts
|

Accurate fundamental parameters for lower main-sequence stars

Abstract: We derive an empirical effective temperature and bolometric luminosity calibration for G and K dwarfs, by applying our own implementation of the Infrared Flux Method to multiband photometry. Our study is based on 104 stars for which we have excellent BV(RI ) C JHK S photometry, excellent parallaxes and good metallicities.Colours computed from the most recent synthetic libraries (ATLAS9 and MARCS) are found to be in good agreement with the empirical colours in the optical bands, but some discrepancies still rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
301
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(332 citation statements)
references
References 127 publications
(270 reference statements)
28
301
1
2
Order By: Relevance
“…Should its theoretical spectrum F λ (see next Section) be modelled with sufficient precision, and its angular diameter θ accurately measured, its absolute flux would be straightforward to obtain. In practice, its pole-on and rapidly rotating nature, as well as its suspected variability (although longward of 12µm, Aumann et al 1984, and thus of no impact on the colours investigated here) complicate things (also see the discussion in Casagrande et al 2006). In practice, the best approach resorts to the use of a composite absolutely calibrated spectrum for different wavelength regions.…”
Section: St Mag Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Should its theoretical spectrum F λ (see next Section) be modelled with sufficient precision, and its angular diameter θ accurately measured, its absolute flux would be straightforward to obtain. In practice, its pole-on and rapidly rotating nature, as well as its suspected variability (although longward of 12µm, Aumann et al 1984, and thus of no impact on the colours investigated here) complicate things (also see the discussion in Casagrande et al 2006). In practice, the best approach resorts to the use of a composite absolutely calibrated spectrum for different wavelength regions.…”
Section: St Mag Systemmentioning
confidence: 99%
“…Brighter than this threshold the difference between the asinh and Pogson magnitudes is negligible and rapidly goes to zero. This makes the Pogson formulation outlined 7 The only difference is the BV(RI) C absolute calibration in Casagrande et al (2010), which is based on earlier HST spectrophotometry of α Lyr (as reported in Table A2 of Casagrande et al 2006), producing T eff values that differ by only a few Kelvin. However, this difference essentially cancels out when the solar twins are used in the calibrating process; i.e., the absolute calibration derived from Bohlin (2007) agrees with that based on the solar twins.…”
Section: Sloan Digital Sky Survey Ugrizmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations also seem to support a MS broadening in 47 Tuc (Anderson et al 2009 Casagrande et al (2006) to translate the dereddened maximum observed colour split between the bMS and rMS returns Δ log T eff = 0.0185 implying ΔY = 0.144 and Y bMS = 0.39 (Fig. 2).…”
Section: Application To Globular Clustersmentioning
confidence: 90%
“…More recently, Casagrande et al (2006Casagrande et al ( , 2007 further improved the analysis by compiling a much larger sample of K dwarfs with bolometric magnitudes and effective temperatures derived via InfraRed Flux Method (IRFM). The implementation adopted for the IRFM resorted to homogeneous multi-band photometry to determine in a fully self-consistent, (almost) model independent way T eff and M Bol .…”
Section: Introductionmentioning
confidence: 99%